String thermodynamics in and out of equilibrium: Boltzmann equations and random walks - Andrew R. Frey; Ratul Mahanta; Anshuman Maharana; Francesco Muia; Fernando Quevedo; Gonzalo Villa (Journal of High Energy Physics, 2024)
Abstract We revisit the study of string theory close to the Hagedorn temperature with the aim towards cosmological applications. We consider interactions of open and closed strings in a gas of Dp-branes, and/or one isolated Dp-brane, in an arbitrary number d of flat non-compact dimensions and general compact dimensions. Leading order string perturbation theory is used to obtain the basic interaction rates in a flat background, which are shown to be consistent with the random walk picture of highly excited strings that should apply in more general backgrounds. Using the random walk interpretation we infer the structure of more general semi-inclusive string scattering rates and then write down the corresponding Boltzmann equations describing ensembles of highly excited closed and open strings. We organise the interaction terms in Boltzmann equations so that detailed balance becomes manifest. We obtain the equilibrium solutions and show that they reduce to previously computed solutions for d = 0. We further study the behaviour of non-equilibrium fluctuations and find explicit analytic expressions for the equilibration rates (and for the number of open strings in d = 0). Potential implications for an early universe with strings at high temperatures are outlined.